Effect of Task Specific Exercises, Gait Training, and Visual Biofeedback on Equinovarus Gait among Individuals with Stroke: Randomized Controlled Study - Mohamed Elsayed Khallaf; Ahmed Maher Gabr; Eman Elsayed Fayed (Neurology Research International)
Background and Purpose. Equinovarus foot is a common sign after stroke. The aim of this study is to investigate the effect of task specific exercises, gait training, and visual biofeedback on correcting equinovarus gait among individuals with stroke. Subjects and Methods. Sixteen subjects with ischemic stroke were randomly assigned to two equal groups (G1 and G2). All the patients were at stage 4 of motor recovery of foot according to Chedoke-McMaster Stroke Assessment without any cognitive dysfunction. E-med pedography was used to measure contact time, as well as force underneath hind and forefoot during walking. Outcome measures were collected before randomization, one week after the last session, and four weeks later. Participants in G1 received task specific exercises, gait training, and visual biofeedback and a traditional physical therapy program was applied for participants in G2 for 8 weeks. Results. Significant improvement was observed among G1 patients (P≤0.05) which lasts one month after therapy termination. On the other hand, there were no significant differences between measurements of the participants in G2. Between groups comparison also revealed a significant improvement in G1 with long lasting effect. Conclusion. The results of this study showed a positive long lasting effect of the task specific exercises, gait training, and visual biofeedback on equinovarus gait pattern among individuals with stroke.